Urgensi Psikologi Pendidikan dalam Pembelajaran Bahasa Arab - Dadan Mardani; Iis Susiawati (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
This research discusses educational psychology which has a significant contribution in increasing the effectiveness of Arabic language learning. By understanding the learning and teaching process as well as individual student needs. This research uses a literature review method (library research), where the discussion in this research is based on expert opinions and the results of previous research on psychology and the learning process. The results show that educational psychology is very important in learning Arabic, as in learning other languages. The following are several reasons why educational psychology is important in this context, including (1) Understanding the Learning Process, (2) Student Motivation and Engagement, (3) Effective Classroom Management, (4) Assessment and Feedback, and (5) Needs Special for Students. By utilizing these educational psychology concepts, Arabic teachers can create a supportive, motivating, and effective learning environment for all their students.